Comparison of Pain Score Reduction Using Triamcinolone vs. Betamethasone in Transforaminal Epidural Steroid Injections for Lumbosacral Radicular Pain. (December 2015) - McCormick, Zachary; Kennedy, David J.; Garvan, Cynthia; Rivers, Evan; Temme, Kate; Margolis, Shana; Zander, Emily; Rohr, Ashley; Smith, Matthew C.; Plastaras, Christopher
ABSTRACT: Objective: Although the comparative efficacy of particulate vs . nonparticulate steroids for the treatment of radicular pain with transforaminal epidural steroid injection has been investigated, there is minimal literature comparing particulate steroids. The authors aimed to determine whether transforaminal epidural steroid injection with triamcinolone or betamethasone, two particulate corticosteroids, more effectively reduces lumbosacral radicular pain. Design: This is a longitudinal cohort study of 1021 patients (1568 transforaminal epidural steroid injections) who received betamethasone or triamcinolone between January 2006 and October 2007 in an academic spine center. The frequency of greater than 50% pain reduction was compared between groups. Results: This study included 42.4% (433) male and 57.6% (588) female patients, with a mean (SD) age of 54.1 (16.7) yrs. Betamethasone and triamcinolone were used in 78.8% (1235) and 21.2% (333) of subjects, respectively. Significantly more patients who received triamcinolone (44.4% [95% confidence interval, 36.2%–52.8%]) experienced greater than 50% pain reduction at short-term follow-up (1–4 wks) compared with patients who received betamethasone (26.8% [95% confidence interval, 22.7%–31.4%]). Conclusions: Patients who received transforaminal epidural steroid injection with triamcinolone reported more frequent pain relief of greater than 50% at short-term follow-up compared with those who received betamethasone. These findings further develop the literature on comparative effectiveness in epidural steroid injections. However, given the exploratory and retrospective nature of this investigation, further study is needed. Abstract : Supplemental digital content is available in the text.